Flavor characterization of sugar-added pennywort (Centella asiatica L.) juices treated with ultra-high pressure and thermal processes - Arunee Apichartsrangkoon (2018)
The flavor characteristics of pennywort juices with added sugar treated by ultra-high pressure, pasteurization, and sterilization were investigated using solid phase microextraction combined with gas chromatography-mass spectrometry. It was found that sesquiterpene hydrocarbons comprised the major class of volatile components present and the juices had a characteristic aroma due to the presence of volatiles including β-caryophyllene and humulene and α-copaene. In comparison with heated juices, HPP-treated samples could retain more volatile compounds such as linalool and geraniol similar to those present in fresh juice, whereas some volatiles such as α-terpinene and ketone class were apparently formed by thermal treatment. All processing operations produced juice that was not significantly different in the concentration of total volatiles. Practical Application: Pennywort juice is considered a nutraceutical drink for health benefits. Therefore, to preserve all aroma and active components in this juice, a nonthermal process such as ultra-high pressure should be a more appropriate technique for retention of its nutritive values than pasteurization and sterilization. © 2009 Institute of Food Technologists®.